2016
DOI: 10.7554/elife.19593
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal cell turnover across tight junctions based on Kelvin's tetrakaidecahedron cell shape

Abstract: In multicellular organisms, cells adopt various shapes, from flattened sheets of endothelium to dendritic neurons, that allow the cells to function effectively. Here, we elucidated the unique shape of cells in the cornified stratified epithelia of the mammalian epidermis that allows them to achieve homeostasis of the tight junction (TJ) barrier. Using intimate in vivo 3D imaging, we found that the basic shape of TJ-bearing cells is a flattened Kelvin's tetrakaidecahedron (f-TKD), an optimal shape for filling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 42 publications
2
69
2
Order By: Relevance
“…Yokouchi et al have proposed that the basic shape of TJ‐bearing granular cells is a flattened Kelvin’s tetrakaidecahedron (f‐TKD) . This model, which assumed that TJs are regularly formed on the edge of f‐TKD cells, can explain how TJ barriers maintain their structural integrity despite cell turnover, and how the regular stacks of corneocytes are formed.…”
Section: Tight Junctionsmentioning
confidence: 99%
“…Yokouchi et al have proposed that the basic shape of TJ‐bearing granular cells is a flattened Kelvin’s tetrakaidecahedron (f‐TKD) . This model, which assumed that TJs are regularly formed on the edge of f‐TKD cells, can explain how TJ barriers maintain their structural integrity despite cell turnover, and how the regular stacks of corneocytes are formed.…”
Section: Tight Junctionsmentioning
confidence: 99%
“…Immortalized human keratinocytes, HDK1 (human dermal keratinocyte 1), were obtained by transfecting TERT, a mutant form of CDK4 and cyclin D1 into normal human keratinocytes . We used cells at passage around 20 for 3D reconstructed epidermis.…”
Section: Methodsmentioning
confidence: 99%
“…Ipponjima et al observed fine morphological changes in chromosomes of epidermal basal cells in mice that were genetically modified to visualize the nuclei in 3D by two‐photon laser scanning microscopy . 3D live imaging by Yokouchi et al captured dynamic changes in the honeycomb pattern of tight junctions in the granular layer of mice that were genetically modified to detect tight junctions . However, these 3D live imaging techniques used for mice cannot be directly applied to live human tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The granular layer, which is traditionally defined by its appearance on haematoxylin and eosin‐stained skin sections, is the site of the terminal cellular remodelling during differentiation and the site at which tight junctions form between neighbouring cells. Tight junctions create a grid within the granular layer and establish the effective paracellular diffusion barrier of the epidermis . Here, we refer to the layer of epidermal cells that are connected by functional tight junctions as “tight junction layer.” It is dynamic and allows the outward passage of differentiating but still viable cells.…”
Section: The Skin Barrier Depends On Continuous Renewal and Executionmentioning
confidence: 99%